Hidden Meaning: Andrew Lang, H. Rider Haggard, Sigmund Freud, and Interpretation - Psomiades, Kathy (Romanticism and Victorianism on the Net, 2013)
This essay examines the role Andrew Lang played in the circulation of ideas within and among the fields of anthropology, literature, and psychoanalysis in the late nineteenth and early twentieth centuries. Lang popularized anthropologist Edward Tylor’s theories about myth, and championed them against those of the philologist Max Müller. He provided the occasion for novelist H. Rider Haggard’s engagement with these ideas in the novel She, which Haggard dedicated to him, and he drew upon these theories of myth in essays that explain the value of Haggard’s novels. Finally, both Haggard’s novel and Lang’s anthropological writing shaped the work of Sigmund Freud. Attention to Lang’s role as a transmitter of the ideas of others across genres and disciplines allows us to see how central the problem of interpretation was to the disciplinary formation of anthropology, literature, and psychoanalysis.